2009
DOI: 10.1007/s00198-009-1118-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet: effects on offspring bone structure

Abstract: A maternal HF diet during pregnancy increases bone marrow adiposity and alters bone structure in their offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 41 publications
3
38
0
Order By: Relevance
“…Both parameters were restored with additional vitamin K supplementation. In our previous study (32), we also observed femoral bone volume loss in male high fat fed offspring (although not to a significant level), but a femoral bone volume increase in high fat fed female offspring. These results again, suggest potential sex differences in vitamin K utilization.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Both parameters were restored with additional vitamin K supplementation. In our previous study (32), we also observed femoral bone volume loss in male high fat fed offspring (although not to a significant level), but a femoral bone volume increase in high fat fed female offspring. These results again, suggest potential sex differences in vitamin K utilization.…”
Section: Discussionsupporting
confidence: 59%
“…In these mice, a combination of a high fat maternal diet and a high fat offspring diet produced greater effects on offspring VKDP expression levels than each high fat diet period alone. This dietary synergy was still evident in parameters such as female femur length and bone marrow adiposity measured in 30 week old mice using this high fat model (32). Vitamin K is fat soluble, hence, increasing levels of adiposity with increasing age may reduce serum levels of vitamin K, and therefore reduce levels of VKDPs produced by organs other than the liver (eg, bone specific osteocalcin) as the liver could be prioritised for the utilization of vitamin K for clotting fac- levels of Gas6 were associated with obesity (which displayed increased blood pressure (BP)) and insulin resistance in adolescents (34), and Gas6 levels were increased in the secretome from atherosclerotic plaques (35).…”
Section: Discussionmentioning
confidence: 80%
“…Suggestive evidence comes from epidemiologic cohort studies, which report correlations between weight at birth and 1 y of age with bone integrity later in life (7,8). In animal models, gestational nutrition and hormone concentrations affect skeletal microarchitecture, bone mineral content, strength, growth plate morphology, and osteoblast differentiation capability (9)(10)(11)(12)(13)(14). However, the mechanisms remain unknown.…”
mentioning
confidence: 99%
“…Lanham et al [37] used a mouse model of highfat intake, both during pregnancy and/or for the offspring. Offspring samples were taken at 30 weeks of age.…”
Section: Bone Development Studies Using the Mousementioning
confidence: 99%